CHANGES IN THE UDDER PROPERTIES OF CATTLE BREEDS DEPENDING ON THEIR MILK YIELD - Saydaliev Utkir Shodievich (Journals Park Publishing, 2022)
The article presents the results of scientific research conducted to determine the changes in the properties of the udder of cattle depending on their milk yield. The article also contains scientific data on the distribution of cows by udder shapes.
Keywords: selection traits; morphological features; functional features